A multi-objective model for selection of projects to finance new enterprise SMEs in Colombia - Coronado-Hernández, J. R; Pardo-Mora, E. M; Valero-Herrero, M (Journal of industrial engineering and management, 2011)
Purpose: This paper presents a multi-objective programming model for selection of Projects for Financing New Enterprise SMEs in Colombia with objectivity and transparency in every call. Approach: The model has four social objectives, subject to constraint budget and to the requirements of every summons. The resolution procedure for the model is based on principles of goal programming. Findings: Selection projects subject to the impact within the country. Research limitations: The selection of the projects is restricted by a legal framework, the terms of reference and the budget of the summons. Practical implications: The projects must be viable according to the characteristics of every summons. Originality/value: The suggested model offers an alternative for entities that need to evaluate projects of co-financing for the managerial development of the SMEs with more objectivity and transparency in the assignment of resources.